Variabilidade espacial da erodibilidade do solo e relações com a paisagem na Sub-bacia das Posses, Extrema – MG - Avalos, Fabio Arnaldo Pomar (2016)
Losses of soil, water, nutrients, and organic matter, caused by water erosion, are among the greatest threats to sustainable development, food security and conservation of ecosystems. Modeling and spatial representation of the factors that determine the erosive processes are essential for soil conservation. Therefore, the aim of this study was to evaluate the relationship between different components of the landscape with soil erodibility in the Posses small watershed, Extrema, MG. The method used was regression kriging. It was found that there is a relationship between soil erodibility and topographic variables such as landform, topographic wetness index and terrain slope, which affect the spatial variability of soil erosion propensity. The established relationship allowed mapping the erodibility in the sub-basin. The resulting maps provide important information for modeling of erosion processes in the sub-basin, as well as the establishment of soil conservation practices. However, it was identified some discrepancies between the data generated by the model and those obtained directly in erosion plots.